Female Education and Social Change - Mathias Bühler; Leonhard Vollmer; Johannes Wimmer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Does access to education facilitate the emergence of a human capital elite from which social activists, and thus, social change can emerge? Assembling a city-level panel of the political, intellectual, and economic elite throughout German history, we find that the opening of schools providing secondary education for women increased their representation among the human capital elite. These elites challenged the status quo and developed critical ideas that resonated in cities with higher human capital, connecting women to form a social movement. We find no evidence of other city-specific indicators of economic and gender-specific cultural change affecting our results. Differential returns to education are also unrelated to the increasing representation of women among the human capital elite, as the opening of gender-specific schools has no impact on the opposite gender.
Keywords: 330; female education; human capital; women's rights